Opportunities and Challenges of Sensor Networks in Health Care Applications - Jabanjalin Hilda, J.; Srimathi, C. (Asian Journal of Engineering and Applied Technology, 2014)
Healthcare is a promising application of the cloud computing technology. Healthcare network over the cloud has been described in this paper. The existing processes for patients’ vital data collection require a great deal of labor work to collect, input and analyze the information. These processes are usually slow and error prone, introducing a latency that prevents real-time data accessibility. This scenario restrains the clinical diagnostics and monitoring capabilities. A solution has been proposed to automate this process by installing health kiosk and integrate the devices. The information becomes available in the “cloud” from where it can be processed by expert systems and or distributed to medical staff. This design is able to make the system more user-friendly while retaining all the benefits of more complicated processes.